11 - Book Review: United Nations Conference on Trade and Development (UNCTA FDI in Least Developed Countries at a Glance, UNCTAD/ITE/IIA/3, 2001. pp. 150.: by Nelson Ο. Magbagbeola - Magbagbeola Nelson Ο. (Africa Development, 2001)
Nelson Ο. Magbagbeola is at the National Centre for Economic Management and Administration Ibadan, Nigeria.